Histopathological Evaluation of the Effect of Eugenol in a Model of Trinitrobenzenesulfonic Acid-Induced Colitis in Rats - Marinov V. (Sciendo, 2021)
Introduction: Trinitrobenzenesulfonic acid (TNBS)-induced experimental colitis in animals is a commonly used model of inflammatory bowel disease (IBD). Eugenol (Eug) is a natural phenolic compound possessing promising antioxidant and anti-inflammatory therapeutic properties.